Beyond transdisciplinarity: Tridifferential Relational Logic as an epistemic strategy for a complex and sustainable university - Díaz-Barrera, Nicolás; Lavanderos, Leonardo (Frontiers in Education, 2025)
Transdisciplinarity (TD) arose as a language of complexity against disciplinary fragmentation; yet its institutional translation under quality-assurance regimes and “client” semantics has tended to commodify knowledge and produce cognitive alienation, thereby neutralizing its transformative force. This article does not seek to replace TD, but to re-read and safeguard it through Tridifferential Relational Logic (LRT)—a non-ontological relational logic that makes the observer explicit and analyzes the co-emergence of function, position, and meaning. In this register, knowledge is no longer treated as transferable content but as a situated symbolic distinction within complex relational fields, consistent with the view of life as a relational unit and ecopoiesis as the symbolic regeneration of relations. Consequently, university “sustainability” cannot be reduced to operational efficiency or indicator management; it must be understood as relational viability—the capacity to sustain tension, host difference, and produce meaning without premature closure. LRT operates as both a critical epistemology and a strategic instrument to imagine the university not as a functional system that optimizes offers in a market, but as an ecology of symbolic relations capable of resisting the supply–demand recoding documented in strategic planning and quality-assurance devices.